"Everyone thought I was a very very bad person… no one want to know you like the nurses and doctors": Using focus groups to elicit the views of adults with learning disability who use challenging behaviour services. (21st August 2017) - Haydon‐Laurelut, Mark; Edmonds, Jane; Daynes, Shona; Clare, Amy; Byles, Rosalind; Barber, Victoria
Accessible summary: We wanted to find out what adults with learning disabilities who receive challenging behaviour services thought about challenging behaviour and the services they receive. We met with people in small groups and talked with them about challenging behaviour. There were barriers to attending the groups like services not having enough staff or transport. People in the groups told us what they thought of words like challenging behaviour, what they understood about challenging behaviour services, and what it was like meeting with them. Abstract: Background: Following scandals such as Winterbourne view, Department of Health, (A national response to Winterbourne View Hospital, 2012) seeks changes in challenging behaviour services. A key part of this change is ensuring people with learning disabilities who use challenging behaviour services have more personalised support and their voices are heard. Materials and Methods: This article describes a study that used focus groups to explore challenging behaviour and challenging behaviour services with people with learning disabilities who used community‐based challenging behaviour services. We analysed the focus groups using thematic analysis. Results: We found three main themes: Engaging with service terminology: the language of Challenging Behaviour; Locating and Framing behaviour; and Engaging with Professionals. Conclusion: People with learning disabilities who receive challenging behaviour services are able to participate in focus groups and tell us about their experiences. Further consideration is required concerning how people with learning disabilities experience their engagement with challenging behaviour services. This study has led to a larger study currently in progress.